An Online Assistant for Remote, Distributed Critiquing of Electronically Submitted Assessment - Penny Baillie-de Byl (Educational technology & society, 2004)
This paper outlines the architecture for an online assessment management system implemented at the University of Southern Queensland. The system assists teams of academics in the management and marking of electronically submitted student assignments in large-scale classes. The system designed to provide a flexible yet structured method for providing feedback to students also offers semi-automatic file handling and grade recording. The system, Classmate, allows a team of markers to access and mark student assignments through a web interface designed to parallel paper-based marking systems. An online authoring tool replaces the red pen on paper analogy. A pilot study conducted on the use of Classmate has found the system to be of use in providing students with consistent feedback, allowing traditional assignment interactions and reducing trivial and repetitive assignment marking tasks.